2020
DOI: 10.1108/mrr-04-2020-0196
|View full text |Cite
|
Sign up to set email alerts
|

Divestiture strategy, CEO power and firm performance

Abstract: Purpose This study aims to examine the moderating role of chief executive officer (CEO) power on the relationship between divestiture strategy and firm performance by framing the relationship under the agency and power circulation theories. Design/methodology/approach This study focuses on a sample of 319 non-financial public-listed companies in Malaysia from the year 2012–2016 and estimates the model under two-step generalized method of moments panel regression to eliminate the endogeneity issue. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
7
0
2
Order By: Relevance
“…In this period, the ministry of Textiles shall play a very decisive role in supporting the sector and especially the S.M.E.’s. Authors (Kolev, 2016 ; Brahmana et al 2021 ; Konara and Ganotakis, 2020 ) recommend a diversification strategy through which the firms can achieve funding by selling their subsidiaries. Such a strategy not only a generates extra cash flow but also transforms the organization in a competitive and planned way.…”
Section: Discussionmentioning
confidence: 99%
“…In this period, the ministry of Textiles shall play a very decisive role in supporting the sector and especially the S.M.E.’s. Authors (Kolev, 2016 ; Brahmana et al 2021 ; Konara and Ganotakis, 2020 ) recommend a diversification strategy through which the firms can achieve funding by selling their subsidiaries. Such a strategy not only a generates extra cash flow but also transforms the organization in a competitive and planned way.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of CEO power and firm performance look into corporate divestiture (Brahmana et al 2021), outside versus inside CEOs (Zhang and Rajagopalan 2010) and endogeneity issues (Li 2016). Brahmana et al (2021) report that CEO power could curb the adverse effect of corporate divestiture on firm performance and lends support to the entrenchment hypothesis of agency theory and suggests that incentives and bargaining power of CEOs are plausible reasons behind this result.…”
Section: Ceo Power and Firm Performancementioning
confidence: 98%
“…Managerial entrenchment theory finds support from Park et al (2018), who show that the negative relation between CEO hubris and firm performance is aggravated by CEO power. Grounded in power circulation theory, Combs et al (2007) find that powerful CEOs could maintain a dominant coalition in the board and the strategic decisions taken by weaker CEOs result in poor outcome (Adams et al 2005;Brahmana et al 2021). Based on prospect theory, Tang and Crossan (2017) and Tang et al (2011) find that troubled firms might take recourse to risky strategies by hiring dominant CEOs.…”
Section: Theories That Have Received Unanimous Support From Empirical...mentioning
confidence: 99%
“…(2005) suggested that powerful CEOs better implement their decisions and that this has a positive (negative) effect when the CEO makes good (bad) decisions. In general, the literature review shows that the CEO's power based on the stewardship theory has a positive and significant effect on the company's performance (Chen, 2014; Hu and Alon, 2014; Javeed et al ., 2021; Brahmana et al ., 2020). Additionally, previous studies have shown that labor productivity affects company performance (Nguyen et al ., 2019; Yazdanfar, 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%